Effect of Imeglimin on mitochondrial function in patients with type 2 diabetes mellitus: a prospective cohort study - Satheesan, Abhishek; Kumar, Janardanan; Leela, Kakithakara Vajravelu; Murugesan, Ria (Frontiers in Endocrinology, 2025)
BackgroundImeglimin, a novel oral hypoglycemic agent, is known to influence mitochondrial function and glucose metabolism. This study evaluates its effects on glycemic control, mitochondrial DNA (mtDNA) copy number, and telomere dynamics in type 2 diabetes mellitus (T2DM).MethodsType 2 diabetes mellitus patients were assigned to one of four treatment groups: (1) Imeglimin alone, (2) Imeglimin with metformin, (3) Imeglimin with other oral hypoglycemic agents, and (4) Metformin with other oral hypoglycemic agents. Clinical and metabolic parameters, mtDNA copy number, and relative telomere length were assessed at baseline and six months. Statistical analyses included paired t-tests and mixed models.ResultsThe study included participants with a mean age of 55.6 years (57% male, BMI 28.8 kg/m2). HbA1c significantly decreased in the Imeglimin + Other OHA (p < 0.001), Imeglimin + Metformin (p < 0.001), and Metformin + Other OHA (p < 0.001) groups, with a smaller but significant decrease in the Imeglimin monotherapy group (p = 0.04). mtDNA copy number increased significantly in the Imeglimin-based combination groups (p < 0.05) but not with monotherapy (p = 0.18). No serious adverse events were reported. Relative telomere length was only associated with age and changes in LDL-c levels.ConclusionImeglimin-based combination therapy effectively improves glycemic control and mitochondrial function, while monotherapy offers limited benefits. Combination therapy may be preferable for optimizing metabolic outcomes in T2DM. No significant change in telomere length was observed during the short period of time.